1983
DOI: 10.1037/0022-0167.30.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of revisions in the Counselor Rating Form.

Abstract: This was produced from a copy of a document sent to us for microfilming. While the most advanced technological means to photograph and reproduce this document have been used, the quality is heavily dependent upon the quality of the material submitted. The following explanation of techniques is provided to help you understand markings or notations which may appear on this reproduction. 1. The sign or "target" for pages apparently lacking from the document photographed is "Missing Page(s)". If it was possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
314
1
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(323 citation statements)
references
References 17 publications
5
314
1
1
Order By: Relevance
“…Clients rated their trainee therapist on single word attributes (i.e., warm, likable, friendly, expert, reliable, sociable, prepared, sincere, skillful, trustworthy) using a 7-point, Likert-type scale with qualitative anchors at 1 (not very) and 7 (very). The CRF-S has been found to highly correlate with the 36-item Counselor Rating Form (Barak & LaCrosse, 1975) and hold up well under factor analysis (Corrigan & Schmidt, 1983). Items were summed to produce a total Therapist Attributes score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clients rated their trainee therapist on single word attributes (i.e., warm, likable, friendly, expert, reliable, sociable, prepared, sincere, skillful, trustworthy) using a 7-point, Likert-type scale with qualitative anchors at 1 (not very) and 7 (very). The CRF-S has been found to highly correlate with the 36-item Counselor Rating Form (Barak & LaCrosse, 1975) and hold up well under factor analysis (Corrigan & Schmidt, 1983). Items were summed to produce a total Therapist Attributes score.…”
Section: Methodsmentioning
confidence: 99%
“…As a precaution, in case it became necessary to control for therapists in the analysis of supervisor effect on outcome, archival ratings from clients in the style of the shortened Counselor Rating Form (CRF-S; Corrigan & Schmidt, 1983) were also included. Clients rated their trainee therapist on single word attributes (i.e., warm, likable, friendly, expert, reliable, sociable, prepared, sincere, skillful, trustworthy) using a 7-point, Likert-type scale with qualitative anchors at 1 (not very) and 7 (very).…”
Section: Methodsmentioning
confidence: 99%
“…Both laboratory and field research has typically revealed very high scores on perceived counselor expertness, attractiveness, and trustworthiness after very brief contact (e.g., l0 min) or an entire counseling session. Although it had been a goal in constructing the CRF-S to encourage greater use of the lower end of the scales (Corrigan & Schmidt, 1983), Epperson and Pecnik (1985) found the CRF-S to be unsuccessful in this regard.In sum, the CRF is the best instrument available for measuring counselor expertness, attractiveness, and trustworthiness. Consistent use of this instrument is advantageous, because it allows comparison across several studies.…”
mentioning
confidence: 99%
“…Total scores can range from 12 to 84. The CRF-S is highly correlated with the original scale (Corrigan & Schmidt, 1983;Epperson & Pecnik, 1985). Further, the measure demonstrated high internal consistency in the current study (α = .92), and the three factors have been supported through confirmatory factor analysis (Ponterrotto & Furlong, 1985).…”
Section: Secondary Dependent Variable Measuresmentioning
confidence: 55%
“…To assess perceived treatment and clinician credibility, participants completed the CEQ credibility scale (see Appendix F) and the Counselor Rating Form-Short Version (CRF-S; Corrigan & Schmidt, 1983; see Appendix G), respectively. The CEQ credibility scale is derived from patients' summed responses to three cognitively-based items assessing how logical the therapy seems, how successful they think the treatment will be in reducing symptoms, and how confident they would be in recommending the treatment to a friend with similar problems.…”
Section: Secondary Dependent Variable Measuresmentioning
confidence: 99%